DNA Topoisomerases maintain promoters in a state competent for transcriptional activation in Saccharomyces cerevisiae. - Jakob Madsen Pedersen; Jacob Fredsoe; Morten Roedgaard; Lotte Andreasen; Kamilla Mundbjerg; Mogens Kruhøffer; Marie Brinch; Mikkel Heide Schierup; Lotte Bjergbaek; Anni Hangaard Andersen (PLoS Genetics)
To investigate the role of DNA topoisomerases in transcription, we have studied global gene expression in Saccharomyces cerevisiae cells deficient for topoisomerases I and II and performed single-gene analyses to support our findings. The genome-wide studies show a general transcriptional down-regulation upon lack of the enzymes, which correlates with gene activity but not gene length. Furthermore, our data reveal a distinct subclass of genes with a strong requirement for topoisomerases. These genes are characterized by high transcriptional plasticity, chromatin regulation, TATA box presence, and enrichment of a nucleosome at a critical position in the promoter region, in line with a repressible/inducible mode of regulation. Single-gene studies with a range of genes belonging to this group demonstrate that topoisomerases play an important role during activation of these genes. Subsequent in-depth analysis of the inducible PHO5 gene reveals that topoisomerases are essential for binding of the Pho4p transcription factor to the PHO5 promoter, which is required for promoter nucleosome removal during activation. In contrast, topoisomerases are dispensable for constitutive transcription initiation and elongation of PHO5, as well as the nuclear entrance of Pho4p. Finally, we provide evidence that topoisomerases are required to maintain the PHO5 promoter in a superhelical state, which is competent for proper activation. In conclusion, our results reveal a hitherto unknown function of topoisomerases during transcriptional activation of genes with a repressible/inducible mode of regulation.